Aplicación digital enfocada a restauraciones en resina como guía para estudiantes de clínica de la Universidad Antonio Nariño (2023)
Operative management is one of the daily activities that allows returning functionality to dental destruction pathology, bringing more and more advances that make dentistry more conservative and more complex to restore functionality, for this reason an easily accessible mobile tool is created that serves as knowledge in clinical practice.